Grepafloxacin Versus Cefixime as Single-Dose Therapy for Uncomplicated Gonorrhea in Women - Mroczkowski, T. F. (Hindawi Publishing Corporation, 1997)
Objective: To compare the efficacy and tolerance of single-dose grepafloxacin with cefixime for treatment of uncomplicated gonorrhea in women. Methods: Women attending nine sexually-transmitted-disease clinics in the United States who had suspected uncomplicated gonorrhea were enrolled in an open study. Participants were randomized to receive single oral doses of grepafloxacin (400 mg) or cefixime (400 mg), and efficacy was evaluated in those who returned for follow-up assessment 5 to 10 days later. The primary measure of efficacy was microbiological response to therapy as determined by pre- and posttreatment culture results for Neisseria gonorrhoeae. Results: Of 380 patients enrolled, 124 in the grepafloxacin group and 131 in the cefixime group were evaluated for microbiological response. Cervical gonococcal infections were eradicated in 99% of patients in both treatment groups, with only one persistent infection in each group. All pharyngeal (n = 15) and rectal (n = 32) gonococcal infections treated with grepafloxacin were cured, whereas 5 of 16 (31%) pharyngeal and 1 of 38 (3%) rectal infections failed to respond to cefixime. Although a third (123 of 386) of N. gonorrhoeae pretreatment isolates were resistant to penicillin or tetracycline, this had no impact on cure rates. Both drugs were well tolerated, with vaginitis being the most common treatment-related adverse event in each group. Conclusions: This study shows that single-dose grepafloxacin is at least as effective as cefixime for treating women with uncomplicated cervical gonorrhea. Grepafloxacin also appears to be highly effective against extragenital infections.